Leukocyte-Dependent Regulation of Cardiac Fibrosis - Okyere, Ama Dedo; Tilley, Douglas G. (Frontiers in Physiology, 2020)
Physiological distress to the heart can initiate a fibrotic response, which is characterized by an enhanced deposition of extracellular matrix proteins within the interstitium. Mechanisms that effect fibrosis gravely disturb myocardial compliance, and ultimately lead to adverse outcomes like heart failure with heightened mortality. As such, understanding the complexity behind fibrotic remodeling has been a focal point of cardiac research in recent years. Resident cardiac fibroblasts and activated myofibroblasts are known to be integral to the fibrotic response; however, additional cell types may contribute to the development of pathological fibrosis. Leukocytes expand in number after injury and exhibit high plasticity, thus their distinct role(s) in cardiac fibrosis is an ongoing and controversial field of study. This review summarizes current findings, focusing on both direct and indirect leukocyte-mediated mechanisms of fibrosis, which may provide novel targeted strategies against fibrotic remodeling.